Impact of a family-centred early intervention programme in South India on caregivers of children with developmental delays. Issue 11 (22nd May 2022) - Muthukaruppan, Sankar Sahayaraj; Cameron, Cathy; Campbell, Zoé; Krishna, Dinesh; Moineddin, Rahim; Bharathwaj, Aravind; Poomariappan, Bala Murugan; Mariappan, Sathiya; Boychuk, Natalie; Ponnusamy, Ramasubramanian; MacLachlan, Janna; Brien, Marie; et al.
Abstract: Background: This study evaluated the impact on caregiver strain and family empowerment among caregivers of children with disabilities who received training and education as part of a family-centred community-based early intervention programme in South India. Methods: This prospective open cohort longitudinal study compared change from baseline to two years post-intervention among caregivers of the first cohort of children who were enrolled in the programme. Paired t-tests determined effect on the Modified Caregiver Strain Index (MCSI) and Family Empowerment Scale (FES), and p -values were adjusted for multiple comparisons using the False Discovery Rate approach. Results: Of the 308 caregivers (91% women), 44% provided care to children with cerebral palsy and 56% to children with other developmental delays. The mean age of the children at baseline was 3.3 (±1.5 years). The overall mean change from baseline in the FES was 4.1 (95% CI: 3.3, 4.9; p  < 0.001) representing improved empowerment. The mean change for the MCSI score was −3.7 (95% CI: −4.5, −2.9; p  < 0.001) representing reduced caregiver strain. Conclusions: A family-centred early intervention programme that provides training and education to caregivers of children with developmental delays demonstrated positive change in caregiver strain and family empowerment. Implications for Rehabilitation: The well-being of a child is influenced by the well-being of their caregiver. Improving caregiver well-being can help improve care and support for children with developmental delays. A family-centred early intervention therapy programme that includes training and education to caregivers can reduce strain and improve family empowerment.